Henny and her boat : righteousness and resistance in Nazi occupied Denmark - Veisz, Howard S. 2017- (CreateSpace Independent Publishing Platform, 2017)
"Henny and Her Boat provides a fresh perspective on the Danes' defense of their Jewish countrymen during years of Nazi occupation and, ultimately, their heroic rescue of the Danish Jews on a fleet of fishing boats and other small craft. Leo Goldberger, a leading expert on the Danish rescue, hails the book as an "educational gem," which describes the rescue in "riveting detail" by following one participant's rise from youthful bystander to rescuer to armed resister. Henny Sinding, daughter of a Danish navy officer, teamed with a fledgling resistance group to save three hundred Jews on a lighthouse supply boat named Gerda III. Each night for a month Henny bravely escorted Jews from secret rendezvous points to a dockside warehouse and then slipped them past Nazi sentries into Gerda III's cargo hold. Gerda III's crew completed the escape--motoring daily past German warships and mines to unoccupied Sweden. After the rescue Henny's team became one of Denmark's leading sabotage groups, while Gerda III continued to save persons hunted by the Nazis. The story of Gerda III and the people associated with it--Henny; Mix, the dashing young resistance fighter who she loved; and many giants of the Danish resistance--epitomizes the story of a nation that rose from a humbling surrender to battle the Nazis and hand the Gestapo its most glaring defeat"--